Morphology of the sternal gland in workers of Coptotermes gestroi (Isoptera, Rhinotermitidae) - Costa-Leonardo, A. M. (Elsevier B.V., 2006)
The sternal gland is considered the only source of trail pheromones in termites. The morphology of the sternal gland was investigated in workers of Coptotermes gestroi using transmission and scanning electron microscopy. The results showed a small bilobed gland at the anterior part of the fifth abdominal sternite. The cuticular surface of the sternal gland showed a V-shaped structure with two peg sensilla in elevated socket and various campaniform sensilla. Pores and cuticular scale-like protuberances also occur in the glandular area. The ultrastructure showed a gland composed of class I cells and two different types of class 3 cells distinguished by location, different size and electron-density of secretory vesicles. Small class 3 cells (type 1) of the anterior lobe are inserted among class I cells and have weakly electron-dense vesicles associated with mitochondria, glycogen and smooth endoplasmic reticulum. The class 3 cells (type 2) of posterior lobe showed many round electron-lucent vesicles of secretion, abundant free ribosomes and a well-developed Golgi apparatus. Each class 3 cell is connected to the cuticle by a cuticular duct constituted by the receiving canal and the conducting canal. The secretion of class I cells is stored in an inner subcuticular reservoir that is delimited by the microvilli of these cells. This inner reservoir is large and crossed by the campaniform sensilla and ducts of two types of class 3 cells that open outside of the insect body. An exterior reservoir also is present between the fourth and fifth sternite. The complex structure of the sternal gland suggests multicomponents for the trail pheromone in the worker of C gestroi. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: termite; Rhinotermitidae; trail pheromone; exocrine gland